(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
The Covid-19 pandemic highlighted the need for scientific knowledge to be closer to society. During this period, researchers from federal public universities shared the steps taken by science and informed the population on how to deal with the adverse moment of public health. Based on a bibliographic survey, through an exploratory and qualitative study, the work aims to discuss science and scientific dissemination in the context of public universities, responsible for most of the research carried out in the country. It intends to contribute to the understanding of the theme and the importance of institutional implementation of the activity in the university environment.